2015
DOI: 10.2174/156800961508151001105814
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CDK8 and CDK8-interacting Genes as Potential Biomarkers in Breast Cancer

Abstract: CDK8 and its paralog CDK19, in complex with CCNC, MED12 and MED13, are transcriptional regulators that mediate several carcinogenic pathways and the chemotherapy-induced tumor-supporting paracrine network. Following up on our previous observation that CDK8, CDK19 and CCNC RNA expression is associated with shorter relapse-free survival (RFS) in breast cancer, we now found by immunohistochemical analysis that CDK8/19 protein is overexpressed in invasive ductal carcinomas relative to non-malignant mammary tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 41 publications
6
53
0
1
Order By: Relevance
“…More recently, we demonstrated that the same correlations are observed in all principal subtypes of breast cancer and their predictive value is much higher for patients who subsequently underwent systemic adjuvant therapy (either hormonal or chemotherapy), suggesting that CDK8 can impact the failure of systemic treatment in breast cancer. We also found that higher CDK8 protein expression was observed in invasive ductal carcinomas relative to non-malignant mammary tissues [20]. A correlation of CDK8 expression with tumor status, nodal metastasis and stage in breast cancer has also been reported by Xu et al, whose study suggested that CDK8 plays a role in mammary carcinogenesis [21].…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…More recently, we demonstrated that the same correlations are observed in all principal subtypes of breast cancer and their predictive value is much higher for patients who subsequently underwent systemic adjuvant therapy (either hormonal or chemotherapy), suggesting that CDK8 can impact the failure of systemic treatment in breast cancer. We also found that higher CDK8 protein expression was observed in invasive ductal carcinomas relative to non-malignant mammary tissues [20]. A correlation of CDK8 expression with tumor status, nodal metastasis and stage in breast cancer has also been reported by Xu et al, whose study suggested that CDK8 plays a role in mammary carcinogenesis [21].…”
Section: Introductionsupporting
confidence: 54%
“…We have extended our previous analysis of CDK8 expression in breast cancer [20] and investigated correlations between CDK8 and ER expression using a microarray database of 3,491 breast cancer patients. Mean CDK8 expression was 1.79-fold higher among 807 ER-negative patients than among 2,036 ER-positive patients (p < 2E-118, t-test).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CDK8/19 regulation is especially pertinent in cancers, where CDK8 positively regulates several cancer-relevant signaling pathways (5), including Wnt/β-catenin (9), the serum response network (6), TGFβ (10), HIF1α (7), and estrogen receptor (8). CDK8 has been identified as an oncogene implicated in colorectal (9), pancreatic (11), and breast (3,8,12,13) cancers and melanomas (14) and associated with the stem cell phenotype (15). CDK8/19 inhibition also has an antiproliferative effect in a subset of leukemias (16,17).…”
Section: Significancementioning
confidence: 99%
“…Instead, CDK8 acts as a co-regulator of transcription that cooperates with several transcription factors, in most cases enhancing the activity of these factors [3, 4]. CDK8 was found to be upregulated in breast cancers and associated with tumor progression; elevated expression of CDK8 and its interactive proteins has been linked to shorter relapse-free survival of breast cancer patients [2, 5, 6]. McDermott et al [1] now found that CDK8 expression in breast cancers is inversely associated with the expression of ER, a finding that made them investigate if CDK8 could affect ER signaling.…”
mentioning
confidence: 99%